Improvement of professionally-orientational work mechanism among university entrants concerning their future profession choice in the field of physical training and culture - Артем’єв [ V. Artemiev] В. О.; Горбенко [О. Horbenko] О. В.; Хомко [I. Khomko] І. Г. (Slobozhanskyi Herald of Science and Sport, 2013)
Data of scientific-methodical literature that is linked with the problems in the system preparation, retraining and refresher training of the personnel in the field of physical culture and sport are generalized. Professionally-orientational work in institute of higher education of sports type control mechanism is scientifically grounded and its main interrelated and interacting components are defined. Problems of professionally-orientational work mechanism introduction among university entrants in the field of physical culture and sport are defined as an integral part in the system of sports personnel preparation. An organizational structure of the professionally-orientational work center in institute of higher education of sports type in Ukraine is presented and general position of its work concerning improvement of professionally-orientational work mechanism introduction among university entrants in the field of physical culture and sport is developed.